2021
DOI: 10.3389/fimmu.2021.711565
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Vaccines: History, Current State, and Clinical Trials

Abstract: Extracellular vesicles (EVs) are released by most cell types as part of an intracellular communication system in crucial processes such as inflammation, cell proliferation, and immune response. However, EVs have also been implicated in the pathogenesis of several diseases, such as cancer and numerous infectious diseases. An important feature of EVs is their ability to deliver a wide range of molecules to nearby targets or over long distances, which allows the mediation of different biological functions. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 190 publications
(215 reference statements)
0
78
0
Order By: Relevance
“…Tumor-derived exosomes have a certain potential antigenicity and can induce a strong antitumor immune response ( 289 ). Therefore, in addition to being a potential diagnostic marker, some studies have found that these exosomes can play a role as vaccines in CRC.…”
Section: Current Strategies Related To Immunotherapy In Crcmentioning
confidence: 99%
“…Tumor-derived exosomes have a certain potential antigenicity and can induce a strong antitumor immune response ( 289 ). Therefore, in addition to being a potential diagnostic marker, some studies have found that these exosomes can play a role as vaccines in CRC.…”
Section: Current Strategies Related To Immunotherapy In Crcmentioning
confidence: 99%
“…Many studies have already pointed to exosomes as promising tumor biomarkers, and, through their employment in patients, improvements to HNSCC detection and treatment regimens may soon be a reality. Plant- and human tissue-derived exosomes have undergone clinical trials in lung cancer, melanoma, and colorectal [ 76 , 77 , 78 , 79 ]. Most recently, MSC exosomes containing siRNA targeting oncogenic KrasG12D mutations are being employed against pancreatic cancer in a clinical trial (NCT03608631).…”
Section: Prospects For Exosomes In Anticancer Therapymentioning
confidence: 99%
“…EVs have been used as a cell-free vaccine for cancer treatment. DCs were cultured with tumor peptides, and then EVs were collected from them [ 21 , 102 ]. EVs derived from tumor-antigen-activated DCs suppressed tumor growth in a T-cell-dependent manner.…”
Section: Potential Of Evs For Cancer Treatmentmentioning
confidence: 99%